Acrylamide concentrations in grilled foodstuffs of Turkish kitchen by high performance liquid chromatography-mass spectrometry - Kaplan, Olcay; Kaya, Gokce; Ozcan, Cemile; Ince, Muharrem; Yaman, Mehmet (Elsevier Science Bv, 2009)
For over ten years, there has been a considerable interest in determination of acrylamide in foodstuffs. It was known that both protein-rich and carbohydrates-rich foods cooked at high-temperatures can cause acrylamide formation. However, carbohydrates-rich foods such as potato chips and biscuit samples have been the common studied foods compared with protein-rich foods such as meat samples. In this study, determination of acrylamide in these two group foods was examined using HPLC-MS. For this purpose, firstly, the parameters that are thought to affect the response in the HPLC-MS analysis were optimized. The optimized conditions were found to be 0.3 ml min(-1) for flow rate of mobile phase, 40 mu l for injection volume, 5 degrees C for column temperature and 70 V for fragmentor potential. The optimized method was applied for the determination of acrylamide levels in Turkish foodstuffs including grilled meat and chicken samples, potato chips, coffee and biscuit. The obtained concentrations for all studied foods were in the range of 20-250 mu g kg(-1). The results showed that acrylamide concentrations highly varied depending on the kind of food samples. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acrylamide; HPLC-MS; Grilled meat; Potato chips; Chicken